A new chitinozoan assemblage from the Middle Devonian Los Monos Formation (sub-Andean basin, southern Bolivia) and its biozonal implications for Western Gondwana - Camina, Sonia Clara (2024)
Chitinozoans recovered from one section of the Middle Devonian Los Monos Formation in the TCB X-1001-Tacobo borehole, sub-Andean basin of Bolivia, have been analysed. Eleven from the eighteen processed cutting samples yielded specimens that allowed taxonomic study. Eleven genera and thirty-five chitinozoan species were identified from the Los Monos Formation with four of them recorded for the first time in Western Gondwana. Ancyrochitina biconstricta, Ancyrochitina parisi, Angochitina galarzae and Ramochitina boliviensis are among the most relevant taxa restricted to Western Gondwana that support the affinity with this paleocontinent. One new species, Lagenochitina tacobensis sp. nov. is described, and Ramochitina candelariaensis sp. nov. (n. n.) is formally erected. The chitinozoan assemblage reinforces the late Eifelian – middle Givetian age previously proposed by organic-walled phytoplankton and miospores for this section of the TCB X-1001-Tacobo borehole. A new local chitinozoan biozonation based on the chitinozoan assemblages is proposed and a revision of the current chitinozoan biozonation for Western Gondwana and Bolivia is recommended.